Combined Aerobic and Resistance Training to Improve of Forced Vital Capacity (FVC) in Young Athletes - Sianturi, Daniel Suryanto; Sumartiningsih, Sri; Bawang, Rex Jhon (Universitas PGRI Palembang, 2025)
The purpose of this study was to assess the effectiveness of an aerobic and resistance training program in improving forced vital capacity (FVC) in young athletes participating in the DBON program (Desain Besar Olahraga Nasional). The study included 19 participants aged 13 to 16, including 7 boys and 12 girls, who underwent a 15-week training program. To ensure measurement accuracy, FVC values were taken before and after the training program with a spirometer. The intervention resulted in a modest increase in FVC values in the male group, from 3.7±0.4 to 3.7±1.3 liters (p=0.509). Females had significantly lower FVC levels (3.4±1.1 liters vs. 3.9±2.7 liters) (p=0.047). Other variables, such as forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF), showed no significant differences between the male and female groups before and after therapy. These findings indicate that both endurance and strength training can improve vital capacity, but the response may vary by gender. This work can be utilized to build individualized training programs for young athletes, taking into account sex-specific physiological characteristics to increase training effects and sports performance.